2016
DOI: 10.1186/s12913-016-1548-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved drug-use patterns at 6 months post-discharge from inpatient substance use disorder treatment: results from compulsorily and voluntarily admitted patients

Abstract: BackgroundTreatment services to patients with substance use disorders (SUDs), including those mandated to treatment, needs to be evaluated and evidence based. The Norwegian Municipal Health Care Act calls for mandated treatment for persons with “severe and life-threatening substance use disorder” if these individuals are not otherwise willing to be voluntarily treated and consequently risk their lives over drug use. This study aims to examine substance use–related outcomes at 6 months following inpatient treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…This finding suggested that the severity of a SUD was related to the level of mental distress. A previous paper reported improved 6-month follow-up SUD outcomes of the present study (frequency of substance use, injection use, and overdoses), but improved outcomes were reported significantly more frequently in the VA than in the CA group (e.g., 61% versus 37% reported reduction in the frequency of the preferred substance) [37]. The present paper elaborate on these findings; patients that remained abstinent were more likely to show lower levels of mental distress than patients that relapsed at 6 month follow-up..…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This finding suggested that the severity of a SUD was related to the level of mental distress. A previous paper reported improved 6-month follow-up SUD outcomes of the present study (frequency of substance use, injection use, and overdoses), but improved outcomes were reported significantly more frequently in the VA than in the CA group (e.g., 61% versus 37% reported reduction in the frequency of the preferred substance) [37]. The present paper elaborate on these findings; patients that remained abstinent were more likely to show lower levels of mental distress than patients that relapsed at 6 month follow-up..…”
Section: Discussionmentioning
confidence: 48%
“…In 2012, this law was replaced by the NMHCA, §10.2, sanctions involuntary interventions for adult patients with SUDs [25]. In this manuscript, we followed a similar methodology to one used previously [37]. Recruitment for this prospective study continued consecutively between January 2009 and May 2011 from three different publicly funded treatment centres in the south-eastern part of Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Incarceration, non-fatal overdose and cocaine use were significantly associated with an increased hazard of coerced treatment, while daily cannabis use and employment were negatively associated with coerced treatment. The finding that coercion did not lead to measurable improvements in substance use supports evidence that coerced treatment may not effectively decrease substance use [12][13][14][15]. Hence, the prevalence of reported coerced addiction treatment is concerning.…”
Section: Discussionmentioning
confidence: 69%
“…Other studies examining formal coerced addiction treatment among incarcerated PWUD have found that it is less effective at reducing substance use and recidivism when compared to controls [9][10][11][12][13][14]. In a prospective study of PWUD in a Norwegian hospital comparing those coerced by health-care providers to those attending treatment voluntarily, voluntary participants had higher reductions in substance use frequency than coerced participants (61 versus 37%) [15]. Additionally, a systematic review on compulsory drug treatment determined that existing evidence is inconclusive, suggesting potential harms associated with coercive interventions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, findings showed higher levels of mental duress, homelessness, relapse and overdose among adults after discharge from mandated treatment. 5 The sentences should have been written as follows:…”
mentioning
confidence: 99%